2018
DOI: 10.21037/mhealth.2018.08.04
|View full text |Cite
|
Sign up to set email alerts
|

If we build it, will they come? Issues of engagement with digital health interventions for trauma recovery

Abstract: Exposure to traumatic events is extremely common with nearly 75% reported to have experienced one or more traumatic events worldwide. A significant number of those exposed will develop posttraumatic stress disorder (PTSD) along with depression, anxiety, and substance use disorders. Globally, trauma-related mental health disorders are the leading cause of global disability burden, and many of these disorders are caused, or worsened, by exposure to wars, natural and human-caused disasters, and other traumatic ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 97 publications
(126 reference statements)
4
72
0
Order By: Relevance
“…To measure the real-world effects of using MHapps outside of clinical trials, some have suggested investigating and quantifying positive relationships between app usage and mental health outcomes (Carpenter et al, 2016;Yeager & Benight, 2018). This can help avoid "digital placebo effects," which occur when merely the installation of a MHapp can bias individuals' responses towards favourable mental health outcomes (Torous & Firth, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To measure the real-world effects of using MHapps outside of clinical trials, some have suggested investigating and quantifying positive relationships between app usage and mental health outcomes (Carpenter et al, 2016;Yeager & Benight, 2018). This can help avoid "digital placebo effects," which occur when merely the installation of a MHapp can bias individuals' responses towards favourable mental health outcomes (Torous & Firth, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring symptoms is also a prerequisite for measuring mood instability in BP and for delivering interventions that address needs of specific individuals in the moment . Many mobile and wearable technologies are available for individuals to self‐monitor their symptoms, but engagement is a common problem . This study evaluated engagement strategies for individuals with BP to monitor symptoms longitudinally.…”
Section: Introductionmentioning
confidence: 99%
“…Smartphone apps require that users actively record their symptoms, a burden that may decrease engagement with users preferring more automated ways to record symptoms . They also involve subjective measurements, which may lead to less accurate or less biologically relevant markers of symptoms . Sensors and wearable devices allow symptoms to monitored passively and objectively .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations